Logistic organ dysfunction system as an early risk stratification tool after aneurysmal subarachnoid hemorrhage - Sheri Tuzi; Beate Kranawetter; Onnen Moerer; Veit Rohde; Dorothee Mielke; Vesna Malinova (Scientific Reports)
Abstract Aneurysmal subarachnoid hemorrhage (aSAH) not only causes neurological deficits but also influences extracerebral organ functions. The Logistic Organ Dysfunction System (LODS) reliably captures organ dysfunctions and predicts mortality of critically ill patients. This study investigated LODS in the setting of aSAH as a surrogate marker for early brain injury (EBI). Patients with aSAH treated between 2012 and 2020 were retrospectively analyzed. LODS was calculated within 24 h upon admission applying functional parameters for each organ system. The EBI was evaluated based on 1-persistent loss of consciousness, 2-global cerebral edema, and 3-intracranial blood burden. The outcome was assessed with the modified Rankin scale (mRS) at 3-months after ictus (mRS > 2 = unfavorable outcome). A total of 324 patients with a mean age of 55.9 years were included. Severe EBI (EBI grade ≥ 3) was found in 38% (124/324) of patients. Higher LODS score correlated with severe EBI (p < 0.0001) and poor outcome (p < 0.0001). LODS with a cutoff of 7 allowed a reliable discrimination (AUC 78%, p < 0.0001) of patients with severe from those with mild EBI. The LODS-calculation as an early risk stratification and prognostic tool reliably reflected the severity of EBI after aSAH and correlated with outcome.